2017
DOI: 10.3390/ijms18050950
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia, HIF, and Associated Signaling Networks in Chronic Kidney Disease

Abstract: The pathogenesis of chronic kidney disease (CKD) is complex and apparently multifactorial. Hypoxia or decrease in oxygen supply in kidney tissues has been implicated in CKD. Hypoxia inducible factors (HIF) are a small family of transcription factors that are mainly responsive to hypoxia and mediate hypoxic response. HIF plays a critical role in renal fibrosis during CKD through the modulation of gene transcription, crosstalk with multiple signaling pathways, epithelial-mesenchymal transition, and epigenetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 144 publications
1
107
0
3
Order By: Relevance
“…HIF-2α seems to be a hypoxia-specific marker as it is detectable in hypoxia in various organs and tissues. Lui Jing et al had found HIF-2α in patients with ischemic kidney damage and showed the critical value of HIF-2α as a marker of hypoxia [22]. Similarly, HIF-2α could be detected through 1-4 hours in serum after inhalation of CO.…”
Section: Discussionmentioning
confidence: 98%
“…HIF-2α seems to be a hypoxia-specific marker as it is detectable in hypoxia in various organs and tissues. Lui Jing et al had found HIF-2α in patients with ischemic kidney damage and showed the critical value of HIF-2α as a marker of hypoxia [22]. Similarly, HIF-2α could be detected through 1-4 hours in serum after inhalation of CO.…”
Section: Discussionmentioning
confidence: 98%
“…In the kidney, podocytes, distal tubules, collecting ducts, and proximal tubules produce VEGF, which plays an important role in the development and integrity of the nephron and renal interstitium. 28,30) VEGF is mainly regulated by HIF-1 at the transcriptional level and the activity of HIF-1 is dependent on the availability of the HIF-1α subunit. It is still controversial whether HIF-1α is pro-fibrotic or anti-fibrotic due to its different roles in different renal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The most notable of these PHD inhibitors are Roxadustat (FG-4592), Vadadustat (AKB-6548), Daprodustat (GSK1278863), Desidustat (ZYAN-1), and Molidustat (Bay 85-3934), all of which have been developed as orally acting drugs for the treatment of anemia, with the expectation that they will also improve kidney function. HIF can crosstalk with multiple profibrotic signaling pathways, including TGF-β, Notch, NF-κB, and PI3K/Akt pathways, to further regulate renal fibrosis (25 stimulation of stress responses, including tubular epithelial autophagy (ref. 16 and Figure 1).…”
Section: Failed Tubule Cell Repairmentioning
confidence: 99%